2012
DOI: 10.1200/jco.2012.30.15_suppl.7508
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity of crizotinib in advanced non-small cell lung cancer (NSCLC) harboring ROS1 gene rearrangement.

Abstract: 7508 Background: Chromosomal rearrangements of the ROS1 receptor tyrosine kinase gene define a new molecular subset of NSCLC. In cell lines, ROS1 rearrangements lead to expression of oncogenic ROS1 fusion kinases and sensitivity to ROS kinase inhibition. We examined the efficacy and safety of crizotinib, a small molecule tyrosine kinase inhibitor of MET, ALK and ROS, in patients with advanced, ROS1-rearranged NSCLC. Methods: Patients with advanced NSCLC harboring ROS1 rearrangement, as determined using a brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 0 publications
1
56
0
1
Order By: Relevance
“…NCT00858195). 12 Currently, in addition to crizotinib, 3 different ROS1 inhibitors (AP26311 [NCT01449461], ASP3062 [NCT1284192], and AZD1480 [NCT01 12397 and NCT01219543]) are in early phase clinical trials (available at: www.clinicaltrials.gov; accessed August 31, 2012). It remains to be determined whether SLC34A2-ROS1 is a driver mutation in GC.…”
Section: Ros1 In Gastric Cancer/lee Et Almentioning
confidence: 99%
“…NCT00858195). 12 Currently, in addition to crizotinib, 3 different ROS1 inhibitors (AP26311 [NCT01449461], ASP3062 [NCT1284192], and AZD1480 [NCT01 12397 and NCT01219543]) are in early phase clinical trials (available at: www.clinicaltrials.gov; accessed August 31, 2012). It remains to be determined whether SLC34A2-ROS1 is a driver mutation in GC.…”
Section: Ros1 In Gastric Cancer/lee Et Almentioning
confidence: 99%
“…[2][3][4] Preclinical experiments indicate that cell lines harbouring ROS1 fusions are sensitive to the ROS1 kinase inhibitor crizotinib. 5,6 The latest results from Phase I trials of crizotinib also indicate that median progression-free survival in patients with advanced ROS1-rearranged NSCLC was 19.2 months. 7 Scheffler et al found that advanced patients with the ROS1 rearrangement had the best overall survival of all subgroups, including those with EGFR-mutated and ALK-rearranged NSCLCs; these authors estimate that the mean overall survival (OS) of patients receiving chemotherapy and crizotinib is 5.3 years.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 More recently, targeted therapies directed at tumor cells harboring anaplastic lymphoma kinase (ALK) fusions and ROS1 fusions have produced impressive results. 4,5 In addition to EGFR, ALK, and ROS1, there are several other abnormalities that could potentially be treated with drugs already approved for other malignancies or investigational agents. 6 Molecular analysis to support personalized therapeutics has historically been obtained with several methods.…”
Section: Introductionmentioning
confidence: 99%